Zero-Voltage and Zero-Current-Switching Full-Bridge PWM Converter Using Auxiliary Active Clamp - Mr. N.Mahesh; Rao, Mr. Venkateswar; Mr. B.Raju (The journal of contemporary issues in business and government, 2017)
Another zero-voltage and zero-current- exchanging (ZVZCS) full-connect (FB) pulsewidth balance (PWM) converter is proposed to improve the presentation of the recently exhibited ZVZCS FB PWM converters. By including an optional dynamic cinch and controlling the brace switch reasonably, ZVS (for driving leg switches) and ZCS (for slacking leg switches) are accomplished without including any lossy parts or the saturable reactor. Numerous preferences including basic circuit topology, high effectiveness, and ease make the new converter alluring for high-voltage and high-power (>10 kW) applications. The rule of activity is clarified and dissected. The highlights and structure contemplations of the new converter are likewise represented and checked on a 1.8-kW 100-kHz protected entryway bipolar transistor (IGBT)- based exploratory circuit.